APP Deletion Accounts for Age-Dependent Changes in the Bioenergetic Metabolism and in Hyperphosphorylated CaMKII at Stimulated Hippocampal Presynaptic Active Zones - Laßek, Melanie; Weingarten, Jens; Wegner, Martin; Neupärtl, Moritz; Array, Tabiwang N.; Harde, Eva; Beckert, Benedikt; Golghalyani, Vahid; Ackermann, Jörg; Koch, Ina; Müller, Ulrike C.; Karas, Michael; et al. (Frontiers in Synaptic Neuroscience, 2017)
Synaptic release sites are characterized by exocytosis-competent synaptic vesicles tightly anchored to the presynaptic active zone (PAZ) whose proteome orchestrates the fast signaling events involved in synaptic vesicle cycle and plasticity. Allocation of the amyloid precursor protein (APP) to the PAZ proteome implicated a functional impact of APP in neuronal communication. In this study, we combined state-of-the-art proteomics, electrophysiology and bioinformatics to address protein abundance and functional changes at the native hippocampal PAZ in young and old APP-KO mice. We evaluated if APP deletion has an impact on the metabolic activity of presynaptic mitochondria. Furthermore we quantified differences in the phosphorylation status after LTP induction at the purified native PAZ. We observed an increase in the phosphorylation of the signaling enzyme CaMKII only in old APP-KO mice. During aging APP deletion is accompanied by a severe decrease in metabolic activity and hyperphosphorylation of CaMKII. This attributes an essential functional role to APP at hippocampal PAZ and putative molecular mechanisms underlying the age-dependent impairments in learning and memory in APP-KO mice.